Schwannoma of Cervical Sympathetic Chain - Reddy, Gundaram Vikram; Vennila, M. R.; Premkumar, Aradhana; Edwin, Rufus Ranjitsingh; Rekha, Arcot (British Journal of Healthcare and Medical Research, 2022)
Schwannomas may occur spontaneously or in the context of a familial tumour syndrome such as neurofibromatosis type 2 (NF2), schwannomatosis and Carney’s complex. Schwannoma arising from the cervical sympathetic chain is an uncommon benign nerve tumour and is a diagnostic challenge. This tumour most often presents as an asymptomatic solitary neck mass, with slow-growing and rare malignant degeneration. Definitive pre-operative diagnosis may be difficult and investigations are not usually helpful. Diagnosis relies on clinical suspicion and confirmation is often obtained using surgical pathology. Surgical excision is the treatment of choice for this tumour, with recurrence being rare. Horner’s syndrome is a common postoperative neurological consequence but does not appear to cause problems to the patient. we describe our experience with clinical presentation, surgical management, and the outcome of a patient who presented with this pathology.